(Substitution of defatted Soybean Meal For Soybean in Tofu Production) - Wuri Handono, Sri Wuri Handono; Suryati Herman, Atih; Yulistia, Aan (Warta Industri Hasil Pertanian, 1987)
Techno-economic study on using deffated soybean meal as a substitute for soybean in tofu production has been conducted. Eight degree of substitution (5, 10, 15, 20, 25, 30, 35 and 40%) were used in making tofu. Substitution of deffated soybean meal for soybean decreased the yield as well as the oraganoleptic properties of tofu. The substitution was acceptable up to the amount of 20%. The study showed that 20% substitution will be profitable if the price of the meal is less than 47% of the soybean price.